A Review on High-speed Electric Spindle Dynamics Modeling and Vibration Response Research - Dai, Ye; Qiao, Binbin; Chen, Xinda; Pan, Gaofeng (Recent Patents on Engineering, 2025)
BackgroundOne of the main directions of modern technology in the field of precision machining is high-speed operation. The spindle system is commonly utilized in this kind of operation, and the electric spindle is the main preference among high-speed machine tool spindles.ObjectiveHigh-speed electric spindle vibration characteristics affect the machining accuracy of the machine tool and the quality of the workpiece, so the research on high-speed electric spindle vibration characteristics has important engineering practical significance.MethodsThe research status of high-speed electrospindle at home and abroad has been summarized in this paper. Combined with the patents related to the dynamics modelling of electrospindle, the research on the dynamics modelling of high-speed electrospindle is analyzed. On this basis, the computational and analytical methods for the vibration modelling of the electrospindle, including the transfer matrix method and the finite element method, are investigated, the theoretical foundations of these methods are discussed in depth, and the advantages and disadvantages of the methods are evaluated. The applicability and limitations of the two methods are also compared.ResultsThe analysis has shown that the current research on the vibration characteristics of high-speed electrospindle is mainly based on mechanical modal analysis and electromagnetic analysis. At present, the dynamic modeling of the electrospindle mainly includes bearing modeling, shaft bearing modeling, spindle-case modeling, electrospindle electromechanical coupling modeling, electrospindle thermal coupling modeling, etc. The correctness of the modelling theory is verified through experimental and simulation results. Although these models tend to be perfected, they are still insufficient in the case of multiple influencing factors coupling and need further development.ConclusionFinally, through the analysis of the patent and dynamic characteristics related to the high-speed electric spindle, thermal deformation, magnetic tension, material, and other factors should be considered comprehensively, and these factors should be coupled to establish an overall dynamics model for the vibration characteristics analysis. The dynamic modelling, vibration modelling method, and vibration characteristics of the high-speed electric spindle have been summarized in this study, and the outlook is presented.
Keywords: finite element method